The ore minerals under the microscope : an optical guide - Pracejus, Bernhard (Atlases in geoscience., 2015)
The Ore Minerals Under the Microscope: An Optical Guide, Second Edition, is a very detailed color atlas for ore/opaque minerals (ore microscopy), with a main emphasis on name and synonyms, short descriptions, mineral groups, chemical compositions, information on major formation environments, optical data, reflection color/shade comparison with four common/standard minerals of a similar color or grey shade, and up to five high-quality photos for each mineral with scale. In addition, the atlas contains a compilation from some of the prominent publications in the field of ore microscopy prese.